Association of osteoprotegerin with impaired glucose regulation and microalbuminuria: the REACTION study. Issue 1 (December 2015) - Niu, Yixin; Yang, Zhen; Li, Xiaoyong; Zhang, Weiwei; Lu, Shuai; Zhang, Hongmei; Chen, Xueru; Zhu, Lingfei; Xing, Yin; Ning, Guang; Qin, Li; Su, Qing
Abstract Background High osteoprotegerin (OPG) has been reported in association with insulin resistance and type 2 diabetes. We aimed to evaluate the association of serum OPG with impaired glucose regulation (IGR) and microalbuminuria among middle-aged and older Chinese. Methods Serum OPG was measured in 599 individuals with normal glucose regulation, 730 with impaired glucose regulation and 327 newly diagnosed patients with diabetes. Serum OPG was measured using ELISA methods and urine albumin/creatinine ratio was used to determine the urinary albumin excretion. Results Serum OPG levels were significantly higher in subjects with isolated impaired fasting glucose, isolated impaired glucose tolerance, combined impaired fasting glucose/impaired glucose tolerance and diabetes than in those with normal glucose regulation, whereas serum OPG levels were not different in the four groups with dysregulation of glucose metabolism. OPG was associated with a higher risk for IGR (OR 1.108 for each 0.1 μg/l increase in OPG, 95 % CI 1.009–1.117, p  = 0.01) after adjustment for gender, age, BMI, current smoking and alcohol intake, family history of diabetes, homeostasis model assessment of insulin resistance (HOMA-IR), lipid profile; the corresponding OR of combined impaired glucose regulation and type 2 diabetes was 1.121 (95 % CI 1.101–1.141, p  = 0.0005). OPG was associated with the risk of microalbuminuria (OR 1.025, 95 % CI 1.006–1.044, p  = 0.02) after adjustment for gender, age, current smoking, current alcohol intake, family history of diabetes, BMI, waist/hip ratio, HOMA-IR, eGFR and lipid profile. Conclusions Serum OPG level is closely and independently associated with IGR and is an independent risk factor for microalbuminuria.